SPECTRAL ANALYSIS OF HEART RATE VARIABILITY IN PATIENTS WITH CORONARY ARTERY DISEASE - Mubarak, Sadia; Imran Majeed, Syed Muhammad; Khan, Muhammad Alamgir (Pakistan Armed Forces Medical Journal, 2023)
Objective: To carryout frequency domain analysis ofheart rate variability in patients with coronary arterydisease.Methods: Forty coronary artery disease patients with coronary artery stenosis greater than 70% of at least onevessel lumen were included. Patients with diabetes mellitus, atrial fibrillation, structural heart diseases andbundle branch block were excluded. DMS 300 4A Holter monitors were used to obtain long-term 12 leaddigital ECG recordings. Cardio Scan premium luxury software was used for analysis of heart rate variability.Results: The mean values of heart rate variability in patients were TP (2171.70 ± 1028.7), VLF (1661.41 ±807.88), LF (392.71 ± 227.92), HF (112.03 ± 77.90) and LF/HF ratio (4.03 ± 1.75). On comparison with normalreference values there was a significant decrease (p-value < 0.05) in all parameters except VLF (p-value =0.351). TP was reduced in all the patients (100%), VLF in 26 (65%), LF in 36 (90%), HF in 36 (90%) and LF/HFratio in 29 (72.5%) patients. The difference between the frequency of patients with decreased heart ratevariability was statistically significant (p-value < 0.05) except VLF (p-value = 0.082).Conclusion: Heart rate variability decreases significantly in patients with coronary artery disease.